1981
DOI: 10.1021/jm00138a020
|View full text |Cite
|
Sign up to set email alerts
|

N-(Aminophenyl)oxamic acids and esters as potent, orally active antiallergy agents

Abstract: dichloromethane (25 mL). The tan solid was filtered off and suspended in cold (0 °C) DMF (50 mL). Anhydrous ammonia was bubbled through for 10 min, and the resulting solution was allowed to stand at room temperature overnight. The DMF solution was evaporated to dryness under reduced pressure, and the residue was washed with CH2C12 and ether and dried: yield 3.0 g; mp 340-345 °C dec. Method M.7-Chloro-4,9-dihydro-4-methyl-9-oxopyrazolo[5,l-h]quinazoline-2-carbonitrile. 7-Chloro-4,9-dihydro-4-methyl-9-oxopyra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…3,5 Aminobenzonitrile 4 could be obtained by the reaction of 2,4,6-tri¯uorobenzonitrile with an ethanolic solution of ammonia at room temperature following a modi®cation of the method described for the preparation of 2-amino-6-¯uorobenzonitrile. 6 In this reaction, a mixture of the two possible monosubstitution products 4 and 5 in a ratio close to the statistical one was obtained. This mixture was easily separated by column chromatography, isolating both products in 60 and 37% yield, respectively.…”
mentioning
confidence: 66%
See 1 more Smart Citation
“…3,5 Aminobenzonitrile 4 could be obtained by the reaction of 2,4,6-tri¯uorobenzonitrile with an ethanolic solution of ammonia at room temperature following a modi®cation of the method described for the preparation of 2-amino-6-¯uorobenzonitrile. 6 In this reaction, a mixture of the two possible monosubstitution products 4 and 5 in a ratio close to the statistical one was obtained. This mixture was easily separated by column chromatography, isolating both products in 60 and 37% yield, respectively.…”
mentioning
confidence: 66%
“…(500 MHz, CD 3 COCD 3 ) 6.21 (br s, 2 H, NH 2 ),6.38 (ddd, J 10.2, J' 9.5, J0 2.5 Hz, 1 H, 5-H), 6.48 (ddd, J 11.0, J' 2.5 J0 2.0 Hz, 1 H, 3-H); C (75.4 MHz, CD 3 COCD 3 ) 82.5 (C, d, J 19.5 Hz, C-1), 92.8 (CH, dd, J 24.4, J' 24.3 Hz, C-5), 98.0 (CH, d, J 26.1 Hz, C-3), 112.9 (C, CN), 154.8 (C, dd, J 6.0, J' 6.1 Hz, C-2), 165.6 (C, dd, J 252.6, J' 17.0 Hz, C-6), 167.2 (C, dd, J 250.3, J' 16.1 C-4) (Found: C, 54.57; H, 2.67; N, 18.01%. C 7 H 4 F 2 N 2 requires: C, 54.45; H, 2.62; N, 18.18%).…”
mentioning
confidence: 99%
“…Aryl oxamic acid derivatives have various interesting applications [4][5][6][7][8]. In addition, aryl oxamic acids can be used as intermediates for the synthesis of various classes of compounds including heterocycles [9][10][11][12].…”
Section: Commentmentioning
confidence: 99%
“…In the same way the oxalyl (1, 2‐dicarbonyl) group is one of the significant functionality in several biologically active species. Organic molecules with oxamate groups exhibit significant activity such as antimalarial, antiallergy, and most notably anticancer as it is a metabolic inhibitor of LDH . In prior studies, oxamates have been shown to prevent the growth and metastasis of breast, cervical, and liver cancer cells in vitro studies .…”
Section: Introductionmentioning
confidence: 99%